Preliminary Immunochemical Studies to Detect Lard - Sudjana, Dina; Amalia, Lia; Adnan, Saepul (UIN Sunan Gunung Djati Bandung, 2020)
Detection of lard in food using immunochemical methods has been carried out. This method has been applied and developed in food analysis. The purpose of this study was to detect the presence of lard in food. The method used was immunochemical which in this case is tested to its application in food analysis. The principle method is based on the antigen-antibody reaction, between lipids as antigens that can be deposited by antibodies in the agar medium. Antibodies were obtained by inducing lard into the blood vessels of rabbits. This method is based on the antigen-antibody reaction between fat as an antigen and antibodies that contain anti-lard as reagents and the occurrence of precipitation in agar media. The antibody was obtained by inducing lard, pork broth, and pig plasma into the blood vessels of rabbits. The results of this study were significant.